Analisis Kelayakan Tarif Batik Solo Trans (BST) Ditinjau Dari Ability To Pay (ATP) Dan Willingness To Pay (WTP) - Lestari, Maharannisa Widi; , Dr. Nurul Hidayati; , Drs. H. Gotot Slamet, M.T (2016)
Surakarta is a city famous for batik culture, one of the public transport operated in Surakarta namely Batik Solo Trans (BST). The diversity of social groups who use BST become one of the factors to see whether the rates paid by users are in accordance with their ability and willingness to pay. This study was conducted to determine the characteristics of the BST, BST rates based on Ability to Pay (ATP), BST rates based on Willingness to Pay (WTP), as well as the feasibility of BST applicable rates based on the ATP and WTP. This research method is done by field observations and other related agencies. Implementation of this research is done by distributing questionnaires and filling the questionnaire conducted in the bus along the route BST Corridor 1 and Corridor 2 were then analyzed according to the indicators ATP and WTP. Based on the analysis, the majority of passengers BST are women, most professions are students, the majority aimed at both business passengers, most revenue is Rp900.001,00-Rp1.009.050,00 wait time of arrival BST felt appropriate by the user is 6-10 minutes and evaluation of the service is quite satisfactory BST. The results of an analysis of the rate based on ATP for Rp2.000,00 for Student, and Rp3.670,00 to the public. The value of WTP for Rp1.555,00 for Student, and Rp3.458,00 to the public. The current rate is greater than the rate based on the ATP and WTP. There needs to be a review of the rates related parties to comply with the ability and willingness of its users.